THEORETICAL INTERPRETATIONS OF THE ESSENCE OF THE CONCEPT OF CULTURAL RIGHTS - Oleshchenko, Veronika; Varava, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to investigate theoretical interpretations and scientifically sound interpretations of the essence of the concept of cultural rights, to determine the characteristics inherent in cultural rights. Research methods: the methodological basis of the study are general methods of thinking, functional, systemic, structural and synergetic methods. Results: there is a lack of uniform interpretation of cultural rights. According to existing theoretical interpretations, on the one hand, cultural rights are defined as the possibility of free spiritual development, preservation and development of national identity, free access to cultural life and the use of cultural achievements, as well as the possible behavior of public relations actors cultural relations. On the other hand, cultural rights determine the guarantees of the state in ensuring human rights aimed at maintaining the socio-cultural well-being of society, ensuring the cultural and spiritual needs of the individual. Discussion: it is established that the problem of ensuring cultural human rights in Ukraine, first of all, is the lack of a unified interpretation of cultural rights, the definition of characteristics, essential characteristics and their content. The problem of separation and legal definition of cultural rights in the system of human rights in Ukraine in legal science is observed since the independence of Ukraine, the formation of Ukrainian legislation and the system of constitutional human rights. The first years of Ukraine's independence are characterized by the active work of theorists and practitioners on the legal definition of personal, civil and political rights. With the adoption of the Constitution of Ukraine, the formal list of constitutional rights and responsibilities has significantly expanded. This became the basis for new research to determine the content, guarantees and conditions for ensuring and exercising rights and freedoms, which were first enshrined at the constitutional level. One of the priority problems was the classification of new constitutional rights, ie the distribution of rights to a particular group of rights for their further regulation and enforcement. The solution of this question, rightly, was considered not only a matter of theoretical or scientific direction. Because understanding the clear classification and place of subjective rights in the human rights system is a vector for understanding the content and possible behavior, measures of individual freedom, for means and ways to protect against their violation. To understand the legal nature of a group of rights, the primary task is to determine their content through theoretical interpretations and essential characteristics. The topical issue today is to determine the content and essence of cultural rights, because in the context of armed conflict, the issue of national identification is an important issue. And such components are history, language, culture and cultural rights.